Dynamic modeling and control of a multi-robot system during assembly of flexible payloads with kinematic uncertainty - Laliberte, Matthieu (ProQuest Dissertations & Theses, 1996)
The present thesis focuses on the assembly of flexible sheet metal parts by using robots when the parts are improperly grasped. The improper grasps generate an angular misalignment between the contact surfaces of the two parts as they are brought in contact which creates bending moments in the parts as well as poor contact between the parts. A control strategy is proposed to eliminate the moments generated by the part's angular misalignment, and in doing so realign the parts for proper contact. By measuring the moments with a force/moment sensor located at the wrist of the robot, the control law uses a PID control in moment error to calculate an on-line angular correction to the orientation set-point of the part. The performance of the controller is tested for different relative angular misalignment by controlling a single robot-payload system to push against a rigid surface. It is also tested with a multi-robot system where two robots bring sheet metal parts in contact for mating.